Organizational Competence for Servitization - Posselt, Tim (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)
Tim Posselt investigates the factors leading to organizational competence for servitization - a key strategic alternative in times of digitalization and globalization -, and analyses the transformation process servitizing firms undergo. He explores the issue through conceptual research and case studies, and identifies the ability to access and leverage customer knowledge as the foundation of successful servitization. The findings provide valuable insight for managers looking to strengthen their service business, and add to literature on servitization and service-dominant logic.
Keywords: Servitization; Service Innovation; Industrial Services; Industrielle Dienstleistungen; Product-Service Systems; Service-dominant Logic